2015
DOI: 10.4186/ej.2015.19.3.85
|View full text |Cite
|
Sign up to set email alerts
|

Use of Native Promoter-eGFP as a Gene Reporter on Onion Epidermis to Analyze Gene Expression of AVR-Pia, an Avirulence Effector of Rice Blast Pathogen

Abstract: Abstract. Rice blast disease, caused by Magnaporthe oryzae, is a major rice disease over the world. Recent studies have identified avirulence effectors from the blast fungus that trigger rice immune against the pathogen invasion after specific interaction with resistance (R) proteins in rice. AVR-Pia is one of avirulence effectors that correspond to Pia-resistant protein, inducing hypersensitive response (HR). Enhanced Green fluorescent protein (eGFP) was used as a reporter of AVR-Pia expression in this study.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…We clearly demonstrated that fungal penetration is not required for AVR‐Pia expression, as it is induced before penetration and also occurs in the appressoria of Δ pls1 . Previously, AVR‐Pia expression has been reported to occur in well‐melanized appressoria of M. oryzae inoculated onto glass slides (Sornkom et al ., ), when the ability of fungal penetration was blocked by impenetrable artificial membranes. Therefore, AVR‐Pia expression is clearly independent of fungal penetration.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We clearly demonstrated that fungal penetration is not required for AVR‐Pia expression, as it is induced before penetration and also occurs in the appressoria of Δ pls1 . Previously, AVR‐Pia expression has been reported to occur in well‐melanized appressoria of M. oryzae inoculated onto glass slides (Sornkom et al ., ), when the ability of fungal penetration was blocked by impenetrable artificial membranes. Therefore, AVR‐Pia expression is clearly independent of fungal penetration.…”
Section: Discussionmentioning
confidence: 99%
“…Seeds of Shin‐2 rice, which lacks the Pia resistance gene, were sown in plastic seedling pots containing soil with fertilizer (Honens seedling soil; Honen Agri, Co., Niigata, Japan) and grown in a glasshouse for 60 days, or until the seventh leaf stage, when intact leaf sheaths were inoculated by injecting a conidial suspension, as described previously (Sornkom et al ., ). The inoculated leaf sheaths were prepared for microscopy by excising thin layers of sheath epidermal cells that had been in contact with the conidial suspension, and the excised leaf sheath pieces were placed on slides and visualized using a BX‐50 fluorescence microscope (Olympus, Tokyo, Japan) equipped with a U‐MNIBA3 filter set.…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…For molecular identification, mycelium of P. oryzae was inoculated into 2YEG medium (consisting of 2 g/L yeast extract and 10 g/L glucose) in an erlenmeyer flask and incubated at 100 rpm for 3 days at 27°C. Mycelia were then collected on filter paper according to Sornkom et al (2015), while endophytic fungi that had the highest inhibitory ability in the antagonist test were grown on potato dextrose broth (PDB) media (containing the same composition as PDA without the agar). Then, the suspension was incubated for 3 days at 27°C.…”
Section: Molecular Identification Of Pathogenic and Endophytic Fungimentioning
confidence: 99%
“…DNA/RNA sequencing, protein or peptide analysis, nanoparticles detection, and single molecular sieving. Nanopore technology is expected to be the upcoming platform for biotechnology and medical application since it furnishes the ability to analyze the characteristics of biomolecules or even their sub-units at the molecular-scale resolution [3][4][5][6]. Same as other miniaturized systems, it grants following benefits, e.g.…”
Section: Introductionmentioning
confidence: 99%